La propriété spatio-temporelle - Normand, Sylvio (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
Ownership is one of the fundamental notions in the Civil Code and yet far too often writings on the subject have presented a narrow view of it. Obviously, its has a well determined genetic code since its general attributes are usus, fructus, abusus and vis attractiva, while its specific features include exclusivity, perpetuity and absolutism ; still it remains a pliable concept. For on the one hand, though core prerogatives remain with the holder of the right, the attributes and features of ownership may not be so well affirmed, which immediately infers the existence of modalities of the right. Yet on the other, the core may be broken down since the object to such ownership then becomes a source of real rights, thus there is dismemberment. The flexibility of ownership resides in the numerous modifications it can undergo and which all potentially exist in ownership. Before attempting to study various hypotheses leading to the recognition of spatio-temporal ownership, it is indispensible to adopt a wide view of this notion since any other approach cannot produce satisfactory results. Among hypotheses under consideration, introducing a new modality seems the best solution. It does, however, have its drawbacks as the notion of spatio-temporal ownership runs against the grain of qualities inherent in the right of ownership. First of all, the holder of this right only exercices a limited abusus and in this respect he is not alone, for precedents exist with the holders of other means of ownership (substituted property, inalienable property, trust property). Furthermore, there would be an obstruction to the perpetual nature of such ownership. This proposal is, however, to be rejected since the spatio-temporal ownership is perpetual, although discontinuous. Once the initial obstacles are overcome, the introduction of an additional modality of ownership essentially requires the recognition of a fourth dimension in the object of ownership, namely its temporality. An abstract notion if ever there was one, temporality raises the question of the need for conceiving an owned piece of property as being a concrete and materialized thing. Nonetheless, ownership may be dematerialized for in fact, real estate property can be represented as a cube of space and not just a flat plane. The only obstacle to this new modality in ownership would be the impossibility of conceiving innominate changes to the right of ownership. In all the code, case law and authoritative writings presently recognize the capacity of the human mind to conceive additional modifications to rights of ownership. Spatio-temporal ownership depends upon the recognition of the temporal dimension of the object of such right and thereby constitutes a modality of ownership whose peculiarities derive from the individual form of its object. Although recognition of modality in ownership seems to be the only way for arriving at spatio-temporal ownership, we may consider various solutions based upon an arrangement of existing institutions in the law relating to ownership —which would allow the constitution of a spatio-temporal right of ownership. Despite its popularity, usufruct does not seem to us to be a satisfactory answer. Joint ownership is more attractive despite the ever-present expectation of a petition to partition. A covenant between undivided coproprietors would provide, in our opinion however, a delay in such partition and this covenant would be enforceable on both parties and beneficiaries. If doubts persist as to the legality of such a covenant, the revision announced in the proposed Civil Code of Quebec will calm such fears. Besides allowing the postponement of partition for a maximum period of thirty years, this revision will make possible the assignment of a piece of property to a durable end and ipso facto a waiver of partition. One must remain aware of the fact that despite the technique used to avoid partition, the right ownership is plural. It is only by the identification of an additional modality of ownership that there may be true spatio-temporal ownership.